Association of body mass index pre-pregnancy with hypertension disorders of pregnancy in Bantul District Special Region of Yogyakarta - Cahyaningtyas, Ayu; Hakimi, Mohammad (Universitas Gadjah Mada, 2022)
Purpose: This research was to identify the relationship between body mass index pre-pregnancy and the incidence of hypertension in pregnancy in Bantul District in 2020. Methods: This research used a retrospective cohort design based on secondary data from an online maternal cohort with SIPIA Bantul in the Bantul district in 2020. The effect size was calculated using Relative Risk (RR) from bivariate chi-square, multivariate binomial regression, and stratification by Mantel-Haenszel. The total sample of this research was 670 pregnant women. Results: Bivariate analysis results showed that there was body mass index pre-pregnancy (RR: 1.45; CI 95%: 1.220 – 1.730; p-value=0,00), mother age (RR: 1.47; CI 95%: 1.243 – 1.745; p-value=0,00), upper arm circumference (RR: 1.45; CI 95%; 1.194 – 1.761; p-value=0,001), and gestational weight gain (RR: 1,34; CI 95%: 1.123 – 1.598; p-value=0,002) have significant association with hypertension in pregnancy in Bantul District 2020. The multivariate analysis showed that body mass index pre-pregnancy and mother's age were the most significant variables with hypertension in Bantul District 2020. The stratification analysis showed that maternal age, upper arm circumference, gestational weight gain, and parity were not confounding. Still, there were modifying effects between body mass index pre-pregnancy and the incidence of hypertension in pregnancy in Bantul District in 2020. Conclusion: Pregnant women who are overweight and obese can increase the incidence of hypertension in pregnancy in Bantul District 2020. Collaboration with nutritionist workers needs to be done to reduce the incidence of hypertension in pregnancy in Bantul District.